A Randomized Controlled Trial of Isoniazid to Prevent Mycobacterium tuberculosis Infection in Kenyan Human Immunodeficiency Virus–Exposed Uninfected Infants. (21st June 2020) - LaCourse, Sylvia M; Richardson, Barbra A; Kinuthia, John; Warr, A J; Maleche-Obimbo, Elizabeth; Matemo, Daniel; Cranmer, Lisa M; Mecha, Jerphason; Escudero, Jaclyn N; Hawn, Thomas R; John-Stewart, Grace
Abstract: Background: Human immunodeficiency virus (HIV)–exposed uninfected (HEU) infants in endemic settings are at high risk of tuberculosis (TB). For infants, progression from primary Mycobacterium tuberculosis ( Mtb ) infection to TB disease can be rapid. We assessed whether isoniazid (INH) prevents primary Mtb infection. Methods: We conducted a randomized nonblinded controlled trial enrolling HEU infants 6 weeks of age without known TB exposure in Kenya. Participants were randomized (1:1) to 12 months of daily INH (10 mg/kg) vs no INH. Primary endpoint was Mtb infection at end of 12 months, assessed by interferon-γ release assay (QuantiFERON-TB Gold Plus) and/or tuberculin skin test (TST, added 6 months after first participant exit). Results: Between 15 August 2016 and 6 June 2018, 416 infants were screened, with 300 (72%) randomized to INH or no INH (150 per arm); 2 were excluded due to HIV infection. Among 298 randomized HEU infants, 12-month retention was 96.3% (287/298), and 88.9% (265/298) had primary outcome data. Mtb infection prevalence at 12-month follow-up was 10.6% (28/265); 7.6% (10/132) in the INH arm and 13.5% (18/133) in the no INH arm (7.0 vs 13.4 per 100 person-years; hazard ratio, 0.53 [95% confidence interval CI, .24–1.14]; P = .11]), and driven primarily by TST positivity (8.6% [8/93] in INH and 18.1% [17/94] in no INH; relative risk, 0.48 [95% CI, .22–1.05]; P = .07). Frequency of severe adverse events was similar between arms (INH, 14.0% [21/150] vs no INH, 10.7% [16/150]; P = .38), with no INH-related adverse events. Conclusions: Further studies evaluating TB preventive therapy to prevent or delay primary Mtb infection in HEU and other high-risk infants are warranted. Clinical Trials Registration: NCT02613169. Abstract : HIV-exposed uninfected infants are at high risk of tuberculosis (TB). For infants, progression from primary Mycobacterium tuberculosis infection to TB disease can be rapid. We assessed whether isoniazid prevents primary M. tuberculosis infection.